Generic framework for crystallization processes using the population balance model and its applicability - Shaikh, Latif J.; Bari, Atul H.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2015)
A generic modeling framework for batch cooling crystallization processes has been developed to understand the crystallization process from operational and modeling point of view. The generic framework for crystallization process modeling incorporates the characteristic dimensions of crystals and polymorphic transformation, as well as the hydrodynamic mixing effects in the crystallizer. This Polyhedral Polymorphic Multizonal Population Balance (PPMPBM) model considers bottom-up and top-down approaches for specific systems with specific targets. The PPMPBM framework allows switching between complex and simple models to study different crystallization systems with different scenarios and combination thereof. This framework uses gPROMS software (PSE, UK) and the Microsoft Excel front-end, along with the Polytope module in Matlab, to predict the crystal size and shape evolution as well as supersaturation profiles inside the crystallizer, which can be implemented for various crystallization systems.